Implementasi Prinsip Community Based Tourism (CBT) dalam Pengelolaan Desa Wisata di Desa Tipang, Kecamatan Bakti Raja, Kabupaten Humbang Hasundutan, Sumatera Utara - Muhammad Khadry; Emrizal Emrizal; Mhd. Halfi I Syahputra (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
The tourism village is one of the programs used to explore the potential of the village that is managed as a tourist attraction where the most important thing cannot be separated from the aspect of developing a tourist village, namely the involvement of local communities, the community takes part in planning, organizing, implementing, and evaluating village management. The tour applies the principles of Community Based Tourism (CBT). This study aims to determine the implementation of Community Based Tourism (CBT) principles in the management of the Tipang Tourism Village. The research method is a mix method with qualitative and quantitative descriptive data analysis. The validity of the data used weighting analysis, cross tabulation analysis and data triangulation techniques. Research shows that Tipang Village has moderate potential with a total tourism potential assessment of 464 in classification (B), the characteristics of tourists who visit are dominated by local tourists in groups, in the management of Tipang Tourism Village the manager has implemented 4 of 5 principles of Community Based Tourism (CBT), including economic, social, cultural and environmental principles, but the implementation of the 4 principles of Community Based Tourism (CBT) has not yet had a clear impact on the local community. It is recommended that the local community maintain and preserve the existing tourism potential in the tourist village of Tipang, for managers it is suggested that they can create products by innovating tour packages to attract more visitors and stay longer in the tourist village of Tipang. For the government, there is support for training on community potential development and budget support for the implementation of programs that have been prepared by the manager of the Tipang Tourism Village.